PEMAHAMAN NASABAH BANK MUAMALAT INDONESIA BANDA ACEH TERHADAP AKAD MUDHARABAH - Iskandar Iskandar; Ilhaamie Abdul Ghani Azmi; azian madun (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2012)
Knowledge and understanding of mudharabah products in Islamic banking is necessity for the customers. Mudharabah is one of banking products pose a great risk, because this involves both the investors and the costumers. For the case of Bank Muamalat Indonesia, customer’s lack of understanding on the mudharabah contract may elevate disputes related to the financing offered by the bank as investor and consequently to the consensus of profit sharing ratio. This study aims to discuss and identify the link between the understanding and the conflicts that occur in Bank Muamalat Indonesia Banda Aceh branch. This is a field research that utilized a quantitative approach in gathering data. The results obtained are analyzed using the SPSS software. The finding shows that there is a link between the understanding and the conflicts that occur in Bank Muamalat Indonesia Banda Aceh. The higher level of customer’s understanding towards the product, the smaller risk of conflict may occur. Thus, the data analysis concludes that there is a small positive relationship between customers' understanding of the mudharabah contract and the disputes possibility. =========================================== Pengetahuan dan pemahaman nasabah terhadap produk mudharabah dalam perbankan syariah sangat diperlukan oleh semua nasabah. Mudharabah adalah salah satu produk perbankan yang menimbulkan resiko yang besar, ini karena akad ini melibat dua pihak, yaitu investor dan nasabah. Pada kasus Bank Muamalat Indonesia, kurangnya pemahaman nasabah terhadap produk Mudharabah akan mendatangkan kemungkinan timbulnya sengketa berkaitan pembiayaan yang dikeluarkan oleh bank sebagai shahibul maal dan kesepakatan nisbah pembagian keuntungan. Kajian ini bertujuan untuk membahas dan mengenal pasti kaitan antara kepahaman dengan konflik yang terjadi di Bank Muamalat Indonesia cabang Banda Aceh. Kajian ini merupakan kajian lapangan dengan menggunakan pendekatan kuantitatif dalam mendapatkan data. Temuan data lapangan dianalisis dengan menggunakan SPSS. Kajian ini mendapati bahwa ada kaitan di antara kepahaman dengan konflik yang terjadi di Bank Muamalat Indonesia Banda Aceh. Semakin tinggi tingkat pemahaman nasabah maka semakin kecil risiko terjadi konflik. Analisis data tersebut menunjukkan hubungan positif kecil antara pemahaman nasabah terhadap akad mudharabah dengan risiko konflik.